Severity assessment for lower respiratory tract infections: potential use and validity of the CRB-65 in primary care - Francis, N; Butler, C; Hood, K; Cals, J; Verheij, T; Little, P; Goossens, H; Coenen, S (2011)
AIMS: To explore the potential use of the CRB-65 rule (based on Confusion, Respiratory rate, Blood pressure and age >65 years) in adults with lower respiratory tract infection (LRTI) in primary care. METHODS: Primary care clinicians in 13 European countries recorded antibiotic treatment and clinical features for adults with LRTI. Patients recorded daily symptoms. Multilevel regression models determined the association between an elevated CRB-65 score and prolonged moderately severe symptoms, hospitalisation, and time to recovery. Sensitivity analyses used zero imputation. RESULTS: Respiratory rate and blood pressure were recorded in 22.7% and 31.9% of patients, respectively. A total of 2,690 patients completed symptom diaries. The CRB-65 could be calculated for 339 (12.6%). A score of >1 was not significantly associated with prolonged moderately severe symptoms (odds ratio (OR) 0.42, 95% CI 0.04 to 4.19) or hospitalisations (OR 3.12, 95% CI 0.16 to 60.24), but was associated with prolonged time to self-reported recovery when using zero imputation (hazard ratio (HR) 0.75, 95% CI 0.64 to 0.88). CONCLUSIONS: Respiratory rate and blood pressure are infrequently measured in adults with LRTI. We found no evidence to support using the CRB-65 rule in the assessment of LRTI in primary care. However, it is unclear whether it is of value if used only in patients where the primary care clinician suspects pneumonia. © 2010 Primary Care Respiratory Society UK.